A geroscience approach for Parkinson's disease: Conceptual framework and design of PROPAG-AGEING project. (March 2021) - Pirazzini, Chiara; Azevedo, Tiago; Baldelli, Luca; Bartoletti-Stella, Anna; Calandra-Buonaura, Giovanna; Dal Molin, Alessandra; Dimitri, Giovanna Maria; Doykov, Ivan; Gómez-Garre, Pilar; Hägg, Sara; Hällqvist, Jenny; Halsband, Claire; et al.
Highlights: Several evidences suggest a continuum between ageing and Parkinson's disease. Propagation of inflammaging may play a major role in this process. PROPAG-AGEING is a H2020 funded Consortium. PROPAG-AGEING aims to characterize the contribution of ageing/inflammaging to PD. PROPAG-AGEING envisages omic analysis of de novo PD, controls and centenarians. Abstract: Advanced age is the major risk factor for idiopathic Parkinson's disease (PD), but to date the biological relationship between PD and ageing remains elusive. Here we describe the rationale and the design of the H2020 funded project "PROPAG-AGEING", whose aim is to characterize the contribution of the ageing process to PD development. We summarize current evidences that support the existence of a continuum between ageing and PD and justify the use of a Geroscience approach to study PD. We focus in particular on the role of inflammaging, the chronic, low-grade inflammation characteristic of elderly physiology, which can propagate and transmit both locally and systemically. We then describe PROPAG-AGEING design, which is based on the multi-omic characterization of peripheral samples from clinically characterized drug-naïve and advanced PD, PD discordant twins, healthy controls and "super-controls", i.e. centenarians, who never showed clinical signs of motor disability, and their offspring. Omic results are then validated in a large number of samples, including in vitro models of dopaminergic neurons and healthy siblings of PD patients, who are at higher risk of developing PD, with the final aim of identifying the molecular perturbations that can deviate the trajectories of healthy ageing towards PD development.